2011
DOI: 10.1016/j.astropartphys.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the data from Compton X-ray polarimeters which measure the azimuthal and polar scattering angles

Abstract: a b s t r a c t X-ray polarimetry has the potential to make key-contributions to our understanding of galactic compact objects like binary black hole systems and neutron stars, and extragalactic objects like active galactic nuclei, blazars, and Gamma-Ray Bursts. Furthermore, several particle astrophysics topics can be addressed including uniquely sensitive tests of Lorentz invariance. In the energy range from 10 keV to several MeV, Compton polarimeters achieve the best performance. In this paper we evaluate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 32 publications
(45 reference statements)
5
29
0
Order By: Relevance
“…3). These results are in qualitative agreement with those obtained at 100 keV by a likelihood analysis of the doubly differential cross section [17].…”
Section: Optimal Variable For Polarisation Measurementsupporting
confidence: 82%
See 1 more Smart Citation
“…3). These results are in qualitative agreement with those obtained at 100 keV by a likelihood analysis of the doubly differential cross section [17].…”
Section: Optimal Variable For Polarisation Measurementsupporting
confidence: 82%
“…1 of Ref. [17]). In this expression, φ is the azimuthal angle, that is the angle between the scattering plane and the direction of polarisation of the incident photon.…”
Section: Polarisation Asymmetry and Average Polarisation Asymmetrymentioning
confidence: 99%
“…This is a consequence of the fact that the modulation of azimuthal scattering angles depends on energy (Equation 3, Figure 1). Nonetheless, given the ∼ 21% MDP improvement from Krawczynski (2011), as well as our MDP improvement of 20%, we conclude that roughly 20% is a good rule of thumb for the maximum improvement one can expect when using the MLM.…”
Section: Discussionmentioning
confidence: 99%
“…At the outset of this work, our expectation was that the MDP would improve by up to ∼ 21%, as Krawczynski (2011) showed that the MLM improved the MDP by ∼ 21% over the SM with an idealized Compton polarimeter at 100 keV, and under the assumption that the same number of counts was used in both the SM and MLM. However, as outlined in Section 2.2, the SM event selections must be optimized to give as low an MDP as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation